PERBANDINGAN ANTARA KEPUTUSAN PRESIDEN NOMOR 55 TAHUN 1993 DENGAN PERATURAN PRESIDEN NOMOR 36 TAHUN 2005 SERTA PERATURAN PRESIDEN NOMOR 65 TAHUN 2006 PADA PENGADAAN TANAH YANG DILAKUKAN OLEH PEMERINTAH KOTA BINJAI PADA TAHUN 2005 - Dikko Ammar (Jurnal Hukum Kaidah: Media Komunikasi dan Informasi Hukum dan Masyarakat, 2019)
Public interest cannot be said specifically. The public interest as a concept must go hand in hand with the realization of the state. The state is formed in the public interest, and law is the main means to realize the interest. The law is solely not only to ensure the public interest but also to protect the personal one so that justice can be carried out. Once, it shows how important the public interest is in the life of the state, and in practice it is contradictory to the personal interest. That is why it should be clearly defined. In the Presidential Regulation number 65 of 2006, the criteria are re-loaded, but in contrast to Presidential Decree No. 55 of 1993 the criteria are development for the public interest carried out by the Government or Regional Government which is subsequently owned or will be owned by the Government or the Regional Government, "and includes 7 (seven) activities. Different from Presidential Decree number 55 of 1993, in the criteria for limiting activities for the public interest in Presidential Regulation number 65 of 2006 it is added the word "will" be owned and not given the limit "not used for profit seeking". The method used in this study is to use normative legal research methods. Keywords: Comparison, Presidential Regulation Number 55 and Number 65 of 2016, Land Acquisition